UPAYA PENINGKATAN EFISIENSI TENAGA GURU PROFESIONAL DALAM PENCAPAIAN MUTU PENDIDIKAN - Datu, Yusra (Hunafa: Jurnal Studia Islamika, 2013)
Abstract. This paper discusses efforts to increase the efficiency of utilization of professional teachers for the achievement of quality education. Teachers are professionals who have the duty and responsibility of educating, teaching, guiding, training, directing, and make an assessment and evaluation of students in early childhood education, formal education, elementary education, and secondary education. Education today is in dire need of professional teachers. It is intended for educational interaction between teachers and learners. Human learners not without potential, every student has provided a variety of potential that should be developed in education.Kata kunci: Efisiensi, Guru Profesional,Â  mutu pendidikan